Connectivity and Spatial Integration of Waste Bank Unit Using Space Syntax : (Case: The Klampok Kasri 2 Waste Bank Unit in Malang, Indonesia) - Audri, Delia Suci; Kusdiwanggo, Susilo; Asikin, Damayanti (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2025)
The community waste bank is recognized as an important element in urban waste management, but its effectiveness is often limited by suboptimal spatial configuration, which hinders social interaction and community participation. This study examines the relationship between spatial configuration and social interaction patterns in community waste banks to reveal how spatial layout influences the quality of social interaction at the Klampok Kasri 2 Waste Bank Unit. Space Syntax is employed as a relevant method to analyze the influence of spatial accessibility and connectivity on social behavior. The research focuses on eight waste bank units. Data analysis was carried out using the Space Syntax method and structured observation. The results show a strong correlation between spatial integration and the intensity of social interaction, while connectivity has a moderate influence. Areas with high global integration consistently support more frequent social interaction, whereas spaces with moderate integration levels foster a greater diversity of social activities. These findings contribute to enhancing the effectiveness of community-based waste banks through improved spatial configuration. They also provide a foundation for developing strategic spatial planning guidelines aimed at increasing social interaction and community participation, both of which are critical to supporting sustainable urban waste management.